1989
DOI: 10.1080/0028825x.1989.10410147
|View full text |Cite
|
Sign up to set email alerts
|

Fungi of New Zealand subantarctic Islands

Abstract: A short historical account is given of fungal collections from the New Zealand subantarctic islands. Records of 28 fungus species from Auckland Islands, 27 from Campbell Island, and 9 from Snares Islands are based on collections made by botanists during a small number of brief visits over the period . There are no records from the two other subantarctic island groups, Bounty and Antipodes Islands. Substrates for the majority of fungirecorded are indigenous plant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…McKenzie & Foggo (1989) listed the fungi of the New Zealand Subantarctic Islands. At that time only 49 named species had been reported.…”
Section: Annotated Review Of the Plants And Animals Of The Subantarcticmentioning
confidence: 99%
“…McKenzie & Foggo (1989) listed the fungi of the New Zealand Subantarctic Islands. At that time only 49 named species had been reported.…”
Section: Annotated Review Of the Plants And Animals Of The Subantarcticmentioning
confidence: 99%
“…Records of New Zealand collections of G. lucidum (and earlier synonyms) may belong here too, although collections have not been located. McKenzie & Foggo (1989) (Reid 1967). Cu~ingham (1949a, p. 1) reported that a collection at K labelled Lenzites abietina Fr.…”
Section: Diplomitoporus Domanskimentioning
confidence: 99%
“…Sphaerobolus is commonly known as “artillery fungus” because of its capability of ejecting a gleba up to 6 m from its base [ 19 , 22 , 23 ]. The genus Sphaerobolus has been recorded in various continents, including North and South America, Africa, Asia, Australia, and Europe [ 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. According to Index Fungorum [ 33 ], there are 35 records of the genus Sphaerobolus ; nevertheless, more recent studies by Geml et al [ 20 ] and Vasava et al [ 31 ] have shown that the genus Sphaerobolus consists of four taxonomically distinct species: S. ingoldii , S. iowensis , S. stellatus, and S. jaysukhianus .…”
Section: Introductionmentioning
confidence: 99%